Treatment of Abnormal Vaginal Microbiota before Frozen Embryo Transfer: Case-Report and Minireview to Discuss the Longitudinal Treatment Efficacy of Oral Clindamycin - Haahr, Thor; Elbaek, Helle O.; Laursen, Rita J.; Alsbjerg, Birgit; Jensen, Jørgen S.; Humaidan, Peter (Frontiers in Physiology, 2017)
Abnormal vaginal microbiota (AVM) or bacterial vaginosis (BV) might negatively impact reproductive outcomes of in vitro fertilization (IVF). However, before randomized controlled trials are initiated, it is necessary to establish the optimal treatment for AVM. Metronidazole seems ineffective to treat the biofilm in AVM; thus, clindamycin could be suggested as a relevant antibiotic agent for future intervention based studies. In the present case report, we present the first longitudinal follow-up of the vaginal microbiota with molecular methods during and after oral clindamycin treatment. Furthermore, we review the recent literature with the aim to discuss the optimal AVM treatment in a fertility setting. The patient was 40 years old with secondary infertility of unknown origin. Prior to the present transfer cycle, she had had two failed IVF cycles. The tentative explanation of failed treatment was age-related aneuploidy. However, the patient asked for AVM diagnosis and she was subsequently diagnosed and treated successfully. Unfortunately, the patient did not achieve pregnancy after clindamycin treatment and two subsequent frozen embryo transfer cycles. Taken together, we report an excellent AVM treatment efficacy both short-term and long-term following oral clindamycin treatment. We discuss the potential impact on the vaginal microbiota of co-treatment with estrogen patches in the stimulated frozen embryo transfer cycle. Furthermore, we discuss future aspects of AVM treatment such as the potential impact of estrogen and live biotherapeutic products to positively modulate the microbiota of the reproductive tract.